Iron absorption from two milk formulas fortified with iron sulfate stabilized with maltodextrin and citric acid (2015)
ABSTRACT: Fortification of milk formulas with iron is a strategy widely used, but the absorption of non-heme iron is low. The purpose of this study was to measure the bioavailability of two iron fortified milk formulas designed to cover toddlers’ nutritional needs. These milks were fortified with iron sulfate stabilized with maltodextrin and citric acid. Methods: 15 women (33–47 years old) participated in study. They received on different days, after an overnight fast, 200 mL of Formula A; 200 mL of Formula B; 30 mL of a solution of iron and ascorbic acid as reference dose and 200 mL of full fat cow’s milk fortified with iron as ferrous sulfate. Milk formulas and reference dose were labeled with radioisotopes 59Fe or 55Fe, and the absorption of iron measured by erythrocyte incorporation of radioactive Fe. Results: The geometric mean iron absorption corrected to 40% of the reference dose was 20.6% for Formula A and 20.7% for Formula B, versus 7.5% of iron fortified cow’s milk (p < 0.001). The post hoc Sheffé indeed differences between the milk formulas and the cow’s milk (p < 0.001). Conclusion: Formulas A and B contain highly bioavailable iron, which contributes to covering toddlers’ requirements of this micronutrient.